Social service management at the Netizen Cinta Nursing Home Foundation in Singkawang City - Dita Pratiwi; Rizky Septia Utami Bafadal; Utami Nur (Privietlab, 2026)
This study analyzes the management of social services at the Netizen Cinta Nursing Home Foundation in Singkawang using the POAC management framework (Planning, Organizing, Actuating, and Controlling). A qualitative method with a phenomenological approach was employed to explore the experiences of elderly residents and foundation managers regarding service implementation. Data were collected through in-depth interviews, observations, and documentation. The findings show that the foundation generally meets the basic needs of the elderly, including food, shelter, social interaction, and spiritual support. However, several managerial challenges remain. Planning remains focused on short-term needs without a long-term strategic direction. Organizing is not fully competency-based and relies heavily on volunteers. Service implementation reflects empathetic care but lacks professional standards and structured programs. In addition, monitoring and evaluation are conducted informally, without clear performance indicators. This study contributes to the understanding of elderly social service management in community-based care institutions and highlights the importance of strategic planning, professional service standards, and systematic evaluation to improve the quality and sustainability of elderly care services.